A Neural Network Based Facial Expression Analysis Using Gabor Wavelets - Praseeda Lekshmi.V; Dr.M.Sasikumar (Zenodo, 2008)
Facial expression analysis is rapidly becoming an area of intense interest in computer science and human-computer interaction design communities. The most expressive way humans display emotions is through facial expressions. In this paper we present a method to analyze facial expression from images by applying Gabor wavelet transform (GWT) and Discrete Cosine Transform (DCT) on face images. Radial Basis Function (RBF) Network is used to classify the facial expressions. As a second stage, the images are preprocessed to enhance the edge details and non uniform down sampling is done to reduce the computational complexity and processing time. Our method reliably works even with faces, which carry heavy expressions. : {"references": ["Bai-Ling Zhang,Haihong Zhang and Shuzhi Sam Ge \"Face Recognition\nby Applying Wavelet Subband Representation and Kernel Associative\nMemmory IEEE Transactions on Neural Networks,Vol 15,NO\n1,January 2004,pp 166-177.", "Sami Romdhani, Shaogang Gong and Alexandra psarrou,\"A Multi-view\nNonlinear Active Shape Model using Kernel PCA, BMVC99", "Tsuyoshi Moriyama, Takeo Kanade, Jing Xiao and Jeffrey F. Cohn\"\nMeticulously Detailed Eye region Model and It-s Application to\nAnalysis of Facial Images\", IEEE Transactions on Pattern Analysis and\nMachine Intelligence, Vol.28, No.5, May 2006.", "Chellappa.R, Wilson.C and Sirohey.S, \"Human and machine\nrecognition of faces: A Survey\" In Proc.IEEE, 83(5): 1995, 705-740.", "Hichem Sahbi, Nozha, Boueimma, Tistarelli, J. Bigun, A.K.Jain (Eds),\nand \"Biometric Authentication\"LNCS2539, Springer Verlag Berlin\nHeidelberg 2002, pp: 112-120.", "Stefano Arca, Paola Campadelli, Raffaella anzarotti \"An Automatic\nFeature based Face recognition system\".", "Hui Li, Hui Lin and Guang Yang,\" A New Facial Expression Analysis\nSystem Based on Warp Images\", Proc. of Sixth World Congress on\nIntelligent Control and Automation, Dalian, China, 2006", "Turk. M,Pentland A \"Face Recognition using Eigen Faces\", In Proc. of\nIEEE conference on Computer Vision and Pattern\nRecognition\",1991,pages:586-591.", "Y.Kosaka,K.Kotani,\"Facial Expression Analysis by Kernal Eigen Space\nMethod based on Class Features (KEMC) Using Non-Linear Basis For\nSeparation of Expression Classes \"International Conference on Image\nProcessing (ICIP)2004.\n[10] Hong-Bo Deng, Lian-Wen Jin, Li-Xin Zhen, Ian-Cheng Huang,\"A New\nFacial Expression Recognition Method Based on Local Gabor Filter\nBank and PCA plus LDA\",International Journal of Information\nTechnology Vol.11,No.11.2005.\n[11] Marian Stewrt Bartlett, Javier R, Movellan and Terrence J\nSeinowski,\"Face Recognition by Independent Component Analysis\",\nIEEE Transactions on Neural Networks, Vol.113, No.6, November\n2002.\n[12] Michael J. Lyons, Shigeru Akamatsu, Miyuki Kamachi, Jiro\nGyoba,\"Coding Facial Expressions with Gabor Wavelets\",Proceedings,\nThird IEEE International Conference on Automatic Face and Gesture\nRecognition, April 14-16 1998, Nara Japan, IEEE Computer Society,\npp. 200-205."]}